The green purchase intention of Tupperware products: the role of green brand positioning - Ahmad Miftah Baiquni; Asmai Ishak (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2019)
The study aims to examine the relationship between Green Brand Positioning (GBP), Green Brand Knowledge (GBK), Attitude toward Green Brand (AGB), and Green Purchase Intention (GPI). The type of research is quantitative research with total samples of 315, selected using convenient sampling techniques. Data were collected through a questionnaire. Structural Equation Modeling with Lisrel 8.80 program was employed to analyze the hypotheses. The result shows that all of the hypotheses developed in this study are supported by the data. In other words, GBP positively influences GBK and AGB. At the same time GBK affects positively AGB, and AGB influence GPI positively. These results indicate that if green companies want to increase their consumers’ purchase intention, they should develop marketing strategies and programs that enhance their brand position and the consumer knowledge regarding the importance and benefit of green product which in turn increase a positive attitude of the consumers toward the brand. The limitations of this study are first, most of the respondents are young women; second, the study only uses one brand as the object; and finally, respondents involved in this study are those who ever used the products/brand without considering the belonging of the products.